Heterologous expression of Bixa orellana cleavage dioxygenase 4–3 drives crocin but not bixin biosynthesis. Issue 3 (17th December 2021) - Frusciante, Sarah; Demurtas, Olivia Costantina; Sulli, Maria; Mini, Paola; Aprea, Giuseppe; Diretto, Gianfranco; Karcher, Daniel; Bock, Ralph; Giuliano, Giovanni
Abstract: Annatto ( Bixa orellana ) is a perennial shrub native to the Americas, and bixin, derived from its seeds, is a methoxylated apocarotenoid used as a food and cosmetic colorant. Two previous reports claimed to have isolated the carotenoid cleavage dioxygenase (CCD) responsible for the production of the putative precursor of bixin, the C24 apocarotenal bixin dialdehyde. We re-assessed the activity of six Bixa CCDs and found that none of them produced substantial amounts of bixin dialdehyde in Escherichia coli . Unexpectedly, BoCCD4-3 cleaved different carotenoids (lycopene, β-carotene, and zeaxanthin) to yield the C20 apocarotenal crocetin dialdehyde, the known precursor of crocins, which are glycosylated apocarotenoids accumulated in saffron stigmas. BoCCD4-3 lacks a recognizable transit peptide but localized to plastids, the main site of carotenoid accumulation in plant cells. Expression of BoCCD4-3 in Nicotiana benthamiana leaves (transient expression), tobacco ( Nicotiana tabacum ) leaves (chloroplast transformation, under the control of a synthetic riboswitch), and in conjunction with a saffron crocetin glycosyl transferase, in tomato ( Solanum lycopersicum ) fruits (nuclear transformation) led to high levels of crocin accumulation, reaching the highest levels (>100 µg/g dry weight) in tomato fruits, which also showed a crocin profile similar to that found in saffron, with highly glycosylated crocins as major compounds. Thus, while the bixin biosynthesis pathway remains unresolved, BoCCD4-3 can be used for the metabolic engineering of crocins in a wide range of different plant tissues. Abstract : A carotenoid cleavage dioxygenase from Bixa orellana elicits crocin production in Solanaceae.